2004
DOI: 10.1111/j.1348-0421.2004.tb03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial mRNA Purification by Magnetic Capture‐Hybridization Method

Abstract: A magnetic capture‐hybridization method was developed for purification of bacterial messenger RNA (mRNA) from total RNA by removing 5S, 16S and 23S ribosomal RNAs (rRNA). The quality of mRNA was evaluated by A260nm/A280nm value, denatured gel electrophoresis and RT‐PCR. The results showed that highly purified and intact mRNA was obtained by this method. The magnetic capture‐hybridization is a rapid and simple method for bacterial mRNA purification and has promising potential for improving studies using bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Therefore, prokaryotic rRNAs are often removed before sequencing to improve mRNA detection sensitivity. Different methods have been used to eliminate prokaryotic rRNA, including subtractive hybridization with rRNA-specific probes 7,8 , digestion with exonuclease that preferentially acts on rRNA, poly(A) tail addition to discriminate against rRNA 9,10 , reverse transcription with rRNA-specific primers followed by RNase H digestion to degrade rRNA:DNA hybrids 11 , and gel electrophoresis size separation and extraction of non-rRNA bands 12 .Among these methods, subtractive hybridization and exonuclease digestion have become the most popular owing to the availability of commercial kits from Ambion (MICROBExpress Bacterial mRNA Enrichment kit) and Epicentre (mRNA-ONLY Prokaryotic mRNA Isolation kit). The former kit uses a subtractive hybridization with capture oligonucleotides specific to 16S and 23S rRNAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, prokaryotic rRNAs are often removed before sequencing to improve mRNA detection sensitivity. Different methods have been used to eliminate prokaryotic rRNA, including subtractive hybridization with rRNA-specific probes 7,8 , digestion with exonuclease that preferentially acts on rRNA, poly(A) tail addition to discriminate against rRNA 9,10 , reverse transcription with rRNA-specific primers followed by RNase H digestion to degrade rRNA:DNA hybrids 11 , and gel electrophoresis size separation and extraction of non-rRNA bands 12 .Among these methods, subtractive hybridization and exonuclease digestion have become the most popular owing to the availability of commercial kits from Ambion (MICROBExpress Bacterial mRNA Enrichment kit) and Epicentre (mRNA-ONLY Prokaryotic mRNA Isolation kit). The former kit uses a subtractive hybridization with capture oligonucleotides specific to 16S and 23S rRNAs.…”
mentioning
confidence: 99%
“…Therefore, prokaryotic rRNAs are often removed before sequencing to improve mRNA detection sensitivity. Different methods have been used to eliminate prokaryotic rRNA, including subtractive hybridization with rRNA-specific probes 7,8 , digestion with exonuclease that preferentially acts on rRNA, poly(A) tail addition to discriminate against rRNA 9,10 , reverse transcription with rRNA-specific primers followed by RNase H digestion to degrade rRNA:DNA hybrids 11 , and gel electrophoresis size separation and extraction of non-rRNA bands 12 .…”
mentioning
confidence: 99%
“…After hybridization, rRNA:probe hybrids bind to beads, allowing their subtraction from the solution. 20 Subtractive hybridization is the most commonly used method so far, partly owning to the availabilities of several commercial kits (Table 3.1).…”
Section: Subtractive Hybridization With Rrna-specific Probesmentioning
confidence: 99%
“…Isolation or enrichment of mRNA is, therefore, an important step in metatranscriptomic experiments. Several methods for mRNA recovery from environmental samples have been described, including: 1) subtractive hybridisation (MICROBExpress Bacterial mRNA Enrichment Kit, Ambion; Pang et al, 2004), 2) exonuclease treatment, which preferentially degrades rRNA (mRNA-ONLY Prokaryotic mRNA Isolation kit, EPICENTRE Biotechnologies, Madison; USA), 3) size separation by gel electrophoresis (McGrath et al, 2008), and 4) duplex specific nuclease (DSN) treatment (Yi et al, 2011). A comparation of two of these approaches (MICROBExpress and DSN) indicated that removal efficiencies vary according to RNA integrity and the environment from which the microbial communities are sampled .…”
Section: Mrna Enrichmentmentioning
confidence: 99%